2014
DOI: 10.1371/journal.pone.0089272
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Botrytis Species Is Associated with a Newly Emergent Foliar Disease in Cultivated Hemerocallis

Abstract: Foliar tissue samples of cultivated daylilies (Hemerocallis hybrids) showing the symptoms of a newly emergent foliar disease known as ‘spring sickness’ were investigated for associated fungi. The cause(s) of this disease remain obscure. We isolated repeatedly a fungal species which proved to be member of the genus Botrytis, based on immunological tests. DNA sequence analysis of these isolates, using several different phyogenetically informative genes, indicated that they represent a new Botrytis species, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 43 publications
(58 reference statements)
0
17
0
2
Order By: Relevance
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, ; Sowley et al ., ; Grant‐Downton et al ., ; Shaw et al ., ). Shaw et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, ; Sowley et al ., ; Grant‐Downton et al ., ; Shaw et al ., ). Shaw et al .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, 2003;Sowley et al, 2009;Grant-Downton et al, 2014;Shaw et al, 2016). Shaw et al (2016) found B. cinerea, B. pseudocinerea, B. mali isolates and an undescribed Botrytis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is subtle, showing symptoms such as chlorosis, necrosis and distortion of emerging leaves in the spring. A causative agent had not been formally diagnosed until Grant-Downton et al (2014) identified a fungus isolated repeatedly from infected leaf material as a member of the genus Botrytis. The new species is phylogenetically closest to B. squamosa and B. elliptica (pathogens of onion and lily, respectively) and was named B. deweyae.…”
Section: 'Come Out Come Out Wherever You Are'mentioning
confidence: 99%
“…and other species, including Botrytis deweyae , which cause no visible symptoms on the plant at the initial time of infection, are long-lived, can be isolated from newly grown host tissues, but cause necrotic lesions as the plant moves into a reproductive phase. Cultivated hosts in which this form of infection has been studied include Hemerocallis (Grant-Downton et al, 2014 ), hybrid commercial Primula (Barnes and Shaw, 2002 , 2003 ), and lettuce (Sowley et al, 2010 ). In wild-growing plants, Rajaguru and Shaw ( 2010 ) found widespread infection in leaves of Taraxacum and, to a lesser extent, wild Primula vulgaris .…”
Section: Introductionmentioning
confidence: 99%